Imidacloprid degradation by potential soil bacteria isolated from rice fields in Grobogan, Central Java, Indonesia - MUHAMMAD ALFIYAN HERMAWAN; ARTINI PANGASTUTI; RATNA SETYANINGSIH (Smujo International, 2024)
Abstract. Hermawan MA, Pangastuti A, Setyaningsih R. 2024. Imidacloprid degradation by potential soil bacteria isolated from rice fields in Grobogan, Central Java, Indonesia. Nusantara Bioscience 16: 284-291. Imidacloprid a widely used pesticide is known for its polar nature, resistance to evaporation, and persistence in soil. When concentrations exceed environmental thresholds, imidacloprid can act as a pollutant, disrupting ecosystems, altering soil pH, and decreasing soil fertility. This study aimed to isolate and identify soil bacteria from rice fields capable of degrading imidacloprid and to highlight their potential role in bioremediation. Isolated bacteria are identified based on morphological characteristics, their ability to degrade imidacloprid and through molecular tests using 16S rRNA. Four bacterial colonies were obtained from the isolation results with different morphological variations. The degradation test results showed that the isolates were able to grow in media containing imidacloprid and were able to reduce imidacloprid by 26.66-31.75%. Based on 16S rRNA gene analysis, isolate IT1 was identified as Enterobacterales, IT2 was identified as the Enterobacteriaceae, IT3 as Pectobacterium aroidearum strain CCRMPA670, and IT4 was identified as Bacillus thuringiensis strain FDAARGOS_791.